Protective role of misoprostol in prevention of gentamicin ototoxicity. (May 2017) - Dogan, Murat; Polat, Halil; Yasar, Mehmet; Bayram, Ali; Karatas, Duran; Hira, İbrahim and Kale, Ahmet and Senel, Fatma and Özcan, İbrahim
Abstract: Objectives: To demonstrate potential protective effect of misoprostol on cochlear toxicity caused by gentamicin with electrophysiological tests and histopathological studies. Materials and methods: The study included 80 ears of 40 rats with normal hearing threshold and DPOAE value in both ears. Animals were assigned into 4 groups. The rats were randomized into 4 groups. Group I (n = 10): Gentamicin, Group II (n = 10): Gentamicin plus misoprostol, Group III (n = 10): Saline; Group IV (n = 10): Misoprostol. All drugs used in the study were given once daily for 15 days. DPOAE and ABR measurements were repeated after drug administration. Subsequently, the rats' cochleae were examined histopathologically. Baseline DPOAE and ABR values were compared to those obtained after drug exposure and cochlear toxicity was evaluated in electrophysiological manner. Results: When At baseline, there were no significant differences in DPOAE responses at frequencies of 1001, 1501, 2002, 3003, 4004, 6006 and 7996 Hz among groups. However In DPOAE test, statistically significant difference was observed between the pre-study basal values and post-study results in groups other than gentamicin + misoprostol group. Additionally, It was found that there was a significant difference in DPOAE response at frequency of 4004 Hz obtained at baseline and after drug exposure according to measurements of epithelial vacuolization in stria vascularis. While ABR threshold values were compared at baseline, there were no significant difference in ABR threshold values of left and right ear between groups. Histopathologically it was also found that there were significant differences measurements of epithelial vacuolization in stria vascularis and inflammation among groups (p < 0.05). Conclusion: By these results, misoprostol, a potent antioxidant, has protective effect against cochlear damage, and that may be a safe alternative.